2018
DOI: 10.1245/s10434-018-6450-5
|View full text |Cite
|
Sign up to set email alerts
|

Academic Surgical Oncologists’ Productivity Correlates with Gender, Grant Funding, and Institutional NCI Comprehensive Cancer Center Affiliation

Abstract: Background. A scholar’s h-index is defined as the number of h papers published, each of which has been cited at least h times. We hypothesized that the h-index strongly correlates with the academic rank of surgical oncologists. Methods. We utilized the National Cancer Institute (NCI) website to identify NCI-designated Comprehensive Cancer Centers (CCC) and Doximity to identify the 50 highest-ranked general surgery residency programs with surgical oncology divisions. Demographic data of respective academic su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 35 publications
2
32
0
Order By: Relevance
“…8,10,11,12,13,14,22,28,29 Some medical specialty–specific studies applied basic controls for a small number of author-level variables. 3,4,5,6,7 Second, using ICC articles as our outcome allowed us to study a particular type of solicited article for a large number of medical journals and with a large sample size. Third, to our knowledge, our study is the first to provide journal-specific estimates of gender disparities for a large number of medical journals using consistent methods alongside all-journal averages.…”
Section: Discussionmentioning
confidence: 99%
“…8,10,11,12,13,14,22,28,29 Some medical specialty–specific studies applied basic controls for a small number of author-level variables. 3,4,5,6,7 Second, using ICC articles as our outcome allowed us to study a particular type of solicited article for a large number of medical journals and with a large sample size. Third, to our knowledge, our study is the first to provide journal-specific estimates of gender disparities for a large number of medical journals using consistent methods alongside all-journal averages.…”
Section: Discussionmentioning
confidence: 99%
“…[60][61][62][63][64][65][66] Finally, institutional policies to promote work-life integration, such as programs and grants that target individuals with substantial extraprofessional caregiving responsibilities, have the potential to ensure all faculty have the opportunity to contribute their insights. [88][89][90] The reasons that the included studies 24,30,33,36,37,39 cited to explain the sex gap, such as lack of effective mentorship for women and the disparate influence of familial responsibilities on women, aligned with the reasons that we discussed previously. Another proposed reason was the tendency for women to have more clinical and educational responsibilities than men, which takes away from their time to do academic work.…”
Section: Discussionmentioning
confidence: 68%
“…Thus, the aim of our study was: (1) to evaluate the h-index as a bibliometric predictor of academic rank; and (2) to characterize associations between the h-index and various personal and institutional factors including gender, number of additional degrees, number of National Institutes of Health (NIH) grants, National Cancer Institute Comprehensive Cancer Center (NCI CCC) affiliation, and Doximity ranking. 3…”
Section: Pastmentioning
confidence: 99%
“…5 Additionally, further studies are needed to explore the relationship between career length and h-index, especially given the high proportion of females (60%) at the Assistant Professor rank in our study. 3 , 6 Overall, future studies are needed to counteract the factors contributing to this newly identified gender disparity in the academic productivity of surgical oncologists.…”
Section: Futurementioning
confidence: 99%